The mitochondrial hub gene UCHL1 May serve as a potential biomarker for diagnosing diabetic cardiomyopathy: a comprehensive integration of biological pathways - Chengjie Gao; Yijing Tao; Da Qian; Yafeng Zhou (BMC Medical Genomics)
Abstract Background Diabetic cardiomyopathy (DCM) is a complex clinical syndrome characterized by cardiac systolic and diastolic dysfunction. Research on the underlying mechanism of mitochondrial dysfunction and the involved genes in patients with DCM is limited. Objective We aimed to explore the hub genes and pathways related to mitochondrial dysfunction that affect the progression of DCM. Methods DCM patient datasets (GSE161052, GSE210611 (test sets) and GSE26887 (validation set) were downloaded from the Gene Expression Omnibus (GEO) database. The identification of the differentially expressed genes (DEGs) was performed using the “limma” R package. Mitochondrial dysfunction-related genes (MDRGs) associated with DCM were obtained from the Molecular Signatures Database (MSigDB). Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analyses were carried out to analyse the biological function of mitochondrial dysfunction-related differentially expressed genes (MDRDEGs) via the “ClusterProfiler”, “DOSE”, “org.Hs.eg.db” and “circlize” R packages. The diagnostic value of the hub genes for DCM was confirmed using receiver operating characteristic (ROC) curves in the test and validation groups. Moreover, the functions of the hub genes in the context of DCM were explored via gene set enrichment analysis (GSEA). A protein‒protein interaction (PPI) network of the hub genes was constructed using the GeneMANIA database. Finally, real-time reverse transcription polymerase chain reaction (real-time RT PCR) analysis and western blot analysis were performed to detect the expression levels of UCHL1. Results A total of 705 DEGs and 122 MDRGs closely related to DCM were identified, and 6 MDRDEGs (AGT, KIT, SLC2A1, SLC2A4, TK2, and UCHL1) were obtained and subjected to GO and KEGG enrichment analyses. ROC curve analysis was performed for the test and validation groups. Only the AUC of UCHL1 reached 1.0 in both the test and validation groups, and UCHL1 was identified as a hub gene in DCM. GSEA revealed that multiple biological pathways were activated or inhibited along with alterations in the expression of UCHL1. PPI network analysis revealed that the hub genes interacted with mainly the ASPSCR1, PTPRU, STXBP3, SOCS6 and UCHL5 proteins. There was a reciprocal regulatory relationship between UCHL1 expression and hsa-miR-181a-5p, hsa-miR-193b-3p, hsa-miR-877-5p and hsa-miR-218-5p levels. Finally, real-time RT PCR and western blot analysis revealed that UCHL1 may be used as a potential diagnostic biomarker of DCM. Conclusions In this study, 6 mitochondrial dysfunction-related hub genes related to DCM were identified. The mitochondrial hub gene UCHL1 was demonstrated to be a potential diagnostic biomarker for DCM.